How Are Mechanical, Physiological, and Perceptual Variables Affected by the Rest Interval Between Sets During a Flywheel Resistance Session? - Sabido, Rafael; Hernández-Davó, Jose Luis; Capdepon, Laia; Tous-Fajardo, Julio (Frontiers in Physiology, 2020)
The use of flywheel devices has increased exponentially during the last few years. This may be due to the wide benefits provided after flywheel resistance training, such as increases in muscular strength, muscle hypertrophy and reductions in injury risk among others. Nevertheless, there is a lack of research about how basic training variables (i.e. rest intervals between sets), influence the acute responses during a flywheel resistance session. Thus, the aim of this study was to assess the influence of three different rest intervals (RI) between sets (1 2 or 3 min), during a flywheel squat sessions with two different inertial loads (0.025 and 0.075 kg•m2). Twenty-three participants performed six testing sessions (two inertial loads × three RI) consisting of 4 sets of 11 repetitions. Concentric and eccentric power, lactate concentration ([La]), rating of perceived exertion (RPE) and delayed onset muscular soreness (DOMS) 24h post session were recorded. Both concentric (ES = 0.44-0.71) and eccentric peak power (ES = 0.12-0.49) decreased across sets when the 1 min RI was used, independently of the inertial load used. The 2 min RI protocol entailed significant decreases in concentric peak power (ES = 0.46) only with the higher inertial load (0.075 kg•m2). RPE was higher during the 1 min compared with both the 2 and the 3 min RI protocol using the 0.025 kg•m2 inertial load (ES = 0.61 and 0.65 respectively) and when comparing the 1min RI with the 3min RI protocol using the 0.075 kg•m2 inertial load (ES = 0.68). Both RPE and [La] was higher when using the 1min RI protocol, while DOMS did not differ between protocols. In conclusion, during flywheel training sessions, a short RI (1 min) were insufficient to maintain power output across sets, and was linked to greater physiological and perceptual variables. Two minutes of RI could be enough only when training with light inertial loads. These data can be used by strength and conditioning coaches to optimize the prescription of flywheel resistance training exercises.